The role of teleconnection in the occurrence probability of extreme precipitation over China based on extreme value theory - Kang, Xiaoping; Min, Ruiying; Dai, Juan; Gu, Xihui (Frontiers in Environmental Science, 2022)
Non-stationarity of extreme climate events has been reported worldwide in recent decades, and traditional stationary analysis methods are no longer sufficient to properly reveal the occurrence probability of climate extremes. Based on the 0.25° × 0.25° gridded precipitation data (i.e. CN05.1), stationary and non-stationary generalized extreme value (GEV) and generalized Pareto (GP) are used to estimate occurrence probability of extreme precipitation over China during 1961-2018. Low-frequency oscillation (LFO) indices, such as El Niño-Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), North Atlantic Oscillation (NAO), Southern Annular Mode (SAM), and Pacific Decadal Oscillation (PDO), are included as time-varying covariates in the GEV and GP distributions. Results show that the occurrence probability of extreme precipitation estimated from the GEV and GP distributions shows a significant upward trend in the northwestern and southeastern China, and the opposite trend in the southwestern, central, and northeastern China. In comparison with stationary model, the fitness of extreme precipitation series is improvement for both the GEV and GP distributions if these LFO indices are used as time-varying covariates. Positive ENSO, IOD and PDO tend to cause negative anomalies in the occurrence probability of extreme precipitation in northeastern China and Tibet Plateau, and positive anomalies in southern China; and, positive NAO and SAM phases mainly tend to cause positive anomalies in southern China. The circulation patterns of extreme precipitation anomalies associated with these LFO indices are discussed from aspects of precipitable water, vertical integrated moisture transport, 500-hPa geopotential height field, and 850hPa wind field.